Toc‐Tum mini‐games: An educational game accessible for deaf culture based on virtual reality. Issue 1 (27th August 2019) - Chaves, Edilson M.; Braga, Paulo Bruno de A.; Montenegro, Yuri Fontenelle L.; Rodrigues, Vitória B.; Munguba, Marilene C.; de Albuquerque, Victor Hugo C.
Abstract: Human hearing is an important sense, which complements the other senses, and is essential for children to begin to acquire basic concepts of the world; however, in severe cases of disability, children become marginalized from these benefits. An example of this is with music, a deaf individual is to be able to perceive it. With this in mind, we developed a novel medical expert system based on virtual reality, called Toc‐Tum mini‐games, applying basic concepts of music in an accessible way to the deaf culture. The intelligent proposed system is validated in two different tests: (a) with the target audience to evaluate the interest in the game and (b) with professionals knowledgeable in the field of music or who have had contact with the deaf, evaluate the impact of the game teaching music to the deaf. The tests with the target audience showed that the methods of interaction allowed the children to understand most of the stages and that they were animated during the test days. Regarding the professionals, they were interested in the possibility of using the proposed system in question, even if some modifications in the design had to be made. The results showed that the Toc‐Tum mini‐games is an intelligent tool capable of introducing music in a playful and manageable way using a virtual environment.